Russia-India Economic Cooperation: Current Trends and Promising Directions - Lydia Kulik (Vestnik MGIMO-Universiteta)
The prevailing geopolitical conditions, characterized by Russia's reorientation away from the West and India's steadfast pursuit of an independent foreign and economic policy, present a distinctive prospect for Russia and India to enhance their trade and investment collaboration to a heightened level. Despite the existence of a Special and Privileged Strategic Partnership between the two nations, the volume of bilateral trade and mutual investments has long remained insufficient in comparison to their political ties. Nevertheless, the trade volume between Russia and India is now experiencing rapid growth due to the significant increase in exports of energy, fertilizers, iron and steel, wood products, vegetable and animal oils from Russia to India. This article not only examines this phenomenon but also assesses the necessary conditions to address India's escalating trade deficit with Russia. These prerequisites encompass the expansion of the manufacturing sector in India, the rise in purchasing power of the Indian middle class, and the accelerated development of digitization in both India and Russia. The Indian economy has been notably stimulated by key governmental initiatives led by Narendra Modi, such as "Atmanirbhar Bharat" (or "Self-Reliant India"), "Make in India," "Skill India," and "Startup India," all of which prioritize digital transformation. Russian entrepreneurs demonstrate a keen interest in India's market trends and swiftly adapt to India's evolving demands and capabilities. Similarly, Indian business circles exhibit a growing inclination to acquire knowledge about contemporary Russia. This realignment presents an opportunity to expand trade beyond conventional goods and establish new investment connections between the two countries.